Examining pre-service social studies teachers’ sensitivity levels based on various variables - Ayşegül Çelik (International Journal of Evaluation and Research in Education (IJERE), 2019)
The purpose of this study is to determine whether or not pre-service Social Studies teachers’ interpersonal sensitivity levels significantly vary depending on various variables. The study employed the quantitative model to determine pre-service Social Studies teachers’ sensitivity levels. The survey model was used as a quantitative model. The study group consists of 80 pre-service teachers studying in the Social Studies Teaching department of a state university located in the Central Anatolian Region of Turkey. The study used a personal information form to find out the pre-service teachers’ demographic information. The personal information form includes descriptive information about age, gender, and grade. The study also used the sensitivity. The scale analysis was made via SPSS. The data were analyzed through independent samples t-test and one-way analysis of variance (ANOVA). The data were collected by the researcher in the 2018-2019 academic year. The pre-service Social Studies teachers’ general average of consciousness was found to be high.